2012
DOI: 10.1158/1078-0432.ccr-12-1780
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Galanin and Its Receptor GalR1 as Novel Determinants of Resistance to Chemotherapy and Potential Biomarkers in Colorectal Cancer

Abstract: Purpose: A major factor limiting the effective clinical management of colorectal cancer (CRC) is resistance to chemotherapy. Therefore, the identification of novel, therapeutically targetable mediators of resistance is vital.Experimental design: We used a CRC disease-focused microarray platform to transcriptionally profile chemotherapy-responsive and nonresponsive pretreatment metastatic CRC liver biopsies and in vitro samples, both sensitive and resistant to clinically relevant chemotherapeutic drugs (5-FU an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 42 publications
3
58
0
1
Order By: Relevance
“…Interestingly, the majority of these tumors exhibited significantly higher galanin levels than corresponding noncancerous tissue (Skotheim et al, 2005;Gilaberte et al, 2007;Kim et al, 2007;Sugimoto et al, 2009;Stevenson et al, 2012), similar to observations of human pheochromocytoma (Bauer et al, 1986c). In colon cancers, GAL mRNA levels were observed to increase significantly with tumor size and stage (Kim et al, 2007), and a recent study found a significant correlation between high galanin expression and poorer disease-free survival in colon cancer patients, identifying galanin as a potential biomarker for certain cancer types (Stevenson et al, 2012).…”
Section: Cancersupporting
confidence: 63%
See 3 more Smart Citations
“…Interestingly, the majority of these tumors exhibited significantly higher galanin levels than corresponding noncancerous tissue (Skotheim et al, 2005;Gilaberte et al, 2007;Kim et al, 2007;Sugimoto et al, 2009;Stevenson et al, 2012), similar to observations of human pheochromocytoma (Bauer et al, 1986c). In colon cancers, GAL mRNA levels were observed to increase significantly with tumor size and stage (Kim et al, 2007), and a recent study found a significant correlation between high galanin expression and poorer disease-free survival in colon cancer patients, identifying galanin as a potential biomarker for certain cancer types (Stevenson et al, 2012).…”
Section: Cancersupporting
confidence: 63%
“…Increased GAL 1 expression was also observed in human pituitary adenomas relative to levels in normal human pituitaries (Tofighi et al, 2012), suggesting cancer-promoting properties for GAL 1 , at least in these tumors. Recently, GAL 1 was proposed to contribute to resistance to chemotherapeutic drugs in colon cancer, because GAL 1 silencing led to enhanced chemosensitivity of human colon cancer cell lines (Stevenson et al, 2012). This is somewhat contrary to the finding that advanced colorectal carcinomas often display chromosomal alterations with a loss of the GAL 1 locus on 18q (Knosel et al, 2002).…”
Section: Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…In an in vitro study it was shown that GAL or type 1 G protein-coupled receptor galanin receptor (GALR1) silencing induced apoptosis in drug-sensitive and drug-resistant CRC cell lines. GALR1 silencing caused down-regulation of FLIP1, an endogenous CASP8 inhibitor, and consequently affected the activation of external pathway of apoptosis [16]. This putative apoptosis-protective role of galanin could represent another, as yet unrecognized, aspect of the neuroprotective function of this neuropeptide.…”
Section: Discussionmentioning
confidence: 98%